SIRT6 in Senescence and Aging-Related Cardiovascular Diseases - Li, Xiaokang; Liu, Lin; Li, Tian; Liu, Manling; Wang, Yishi; Ma, Heng; Mu, Nan; Wang, Haiyan (Frontiers in Cell and Developmental Biology, 2021)
SIRT6 belongs to the NAD+-dependent deacetylase sirtuin family and plays pivotal roles in regulating the dynamic balance of the vital movement, including aging and longevity. Its function is similar to the Silent Information Regulator 2 (SIR2), which prolongs life and regulates genomic stability, telomere integrity, transcription, and DNA repair. Deficiency of SIRT6 may induce chronic inflammation, oxidative stress, autophagy etc. In addition, evidence suggests that SIRT6 is a vital factor in inhibiting myocardial hypertrophy and preventing heart failure among elderly patients, suggesting its cardioprotective role. Generally, these findings expose various mechanisms behind the interesting role of SIRT6, however, which are poorly understood. Herein, this narrative review primarily discusses the role of SIRT6 in cell senescence and aging-related cardiovascular diseases. We also summarize clinical application of SIRT6 and potential targeted drug in aging-related cardiovascular diseases.